Methods of adipose tissue distribution measurement by ultrasound: systematic review - Buckus, Bronius; Brimas, Gintautas; Brimas, Gintautas (Lietuvos chirurgija, 2018)
[full article and abstract in Lithuanian; abstract in English] Background / objective The aim of this systematic literature review is to provide a complete overview of ultrasound techniques used for measuring subcutaneous adipose tissue and visceral adipose tissue and distinguish the most appropriate ultrasound technique used for obese patients. Methods The search of the publications was performed using PubMed, Current Contents and Cochrane Library databases. All publications with emphasis on ultrasound measurements of adipose tissue and it’s comparison to computed tomography or magnetic resonance imaging and published before December 1, 2017 were reviewed. Results 17 studies which examined adipose tissue distribution by ultrasound measurements were included in our analysis. A total number of 1 085 patients were evaluated in the included studies. Studies which compared and validated ultrasound measurements with computed tomography and magnetic resonance imaging confirmed slightly inconsistent accuracy for visceral adipose tissue (r = 0.63–0.94) and for subcutaneous adipose tissue (r = 0.33–0.96). Six studies have studied the obese and morbidly obese population (BMI ≥30 kg/m2). In these studies the correlation coefficient between computed tomography and ultrasound was very strong for visceral adipose tissue (r = 0.823) and subcutaneous adipose tissue (r = 0.745). In the morbidly obese group, the reliability of the measurements was excellent (r = 0.94). Conclusions Ultrasound is a relatively inexpensive, non-invasive and available tool which can be used for estimating adiposity in large scale population surveys. We recommend modified Stolk method for the measurement of adipose tissue distribution in obese patients.